Special dentures - Akshayalingam Meenakshi; N Sangeetha Meena; Vinay Bharti; S Suganthapriya (Wolters Kluwer Medknow Publications, 2017)
Although complete dentures cannot be considered as a substitute for, natural teeth, they have been and remain, the staple treatment for edentulous patients. Most of them appear to have benefited from complete denture treatment and report satisfactory oral and masticatory function with their use. Not every case of edentulism, either complete or partial, can be treated with conventional methods of denture fabrication. There is a need for slight modification in impression procedure or designing of the prosthesis to achieve best results in case of compromised conditions. This article intends to highlight clinically relevant modifications of complete denture prosthesis that can be kept in mind, when such cases may be encountered in daily practice.